2022
DOI: 10.3389/fmicb.2022.908461
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine, Isolated From Macleaya cordata, Exhibits Potent Antifungal Efficacy Against Candida albicans Through Inhibiting Ergosterol Synthesis

Abstract: In recent decades, infections caused by the opportunistic fungus Candida albicans have increased, especially in patients with immunodeficiency. In this study, we investigated the mechanism of action of sanguinarine (SAN) against C. albicans both in vitro and in vivo. SAN exhibited antifungal activity against C. albicans clinical isolates, with MICs in the range of 112.8–150.5 μM. Furthermore, scanning electron and transmission electron microscopy showed that SAN induced morphological changes as well as structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The concentration of conidia or spore was adjusted with sterile saline to 1 × 10 4 cells/mL by hemocytometer counts. The antifungal susceptibility testing was performed as outlined in document M38-A2 and previous research, with minor changes [ 16 , 17 , 18 , 19 ]. The medium used was RPMI 1640 with L-glutamine buffered to pH 7.0 with 0.165 M morpholinepropanesulfonic acid (MOPS) and was supplemented with 2% glucose ( m / v ).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of conidia or spore was adjusted with sterile saline to 1 × 10 4 cells/mL by hemocytometer counts. The antifungal susceptibility testing was performed as outlined in document M38-A2 and previous research, with minor changes [ 16 , 17 , 18 , 19 ]. The medium used was RPMI 1640 with L-glutamine buffered to pH 7.0 with 0.165 M morpholinepropanesulfonic acid (MOPS) and was supplemented with 2% glucose ( m / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Another study reported that sanguinarine inhibited 10 C. albicans strains, with the MICs within the range of 37.5-50 µg/mL. Sanguinarine also showed anticandidal effects in a murine model at the dose of 1.5 and 2.5 mg/kg, and the mode of action is related to ergosterol synthesis deficiency in cells [46]. Sanguinarine can also inhibit C. albicans biofilms, and 3.2 µg/mL of sanguinarine significantly inhibits C. albicans biofilm formation by over 90% and destroys mature biofilms by 68.3%.…”
Section: Alkaloidsmentioning
confidence: 97%
“…They are among the major bioactive components of Macleaya cordata ( M. cordata ) [ 3 , 4 ]. Academics and industrial researchers developed a strong interest in these substances because of their significant antimicrobial and animal growth-promoting activities [ 5 , 6 ]; parasiticidal effects [ 7 ]; anti-inflammatory effects [ 8 ]; and anti-tumor activities [ 9 ]. Recently, there has been a steady rise in the daily demand for this particular plant due to its significant commercial worth.…”
Section: Introductionmentioning
confidence: 99%